Meccanomics : the march of the new muslim middle class - Nasr, Vali. ([S.l.] : Oneworld Publications, 2010)
Combining historical narrative with eye-opening on-the-ground research, "Meccanomics" introduces a Muslim world we've never seen before; one that is being transformed by booming economies and a vibrant middle class that will tip the balance away from extremists. This groundbreaking analysis from the author of the "New York Times'" best-selling "The Shia Revival", offers a powerful reassessment of a world where financial might - not fundamentalism - is doing the talking.
Keywords: Capitalism; Capitalists and financiers; Economic history; Islam and politics; Islamic countries; Middle East; Middle class; Political science